1983
DOI: 10.1111/j.1365-3083.1983.tb00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Inbred Mouse as a Model for Experimental Treponema pallidum Infection

Abstract: Mice of several inbred strains were studied for responses to Treponema pallidum (Nichols). Mice were injected with viable treponemes and observed daily for the presence of lesions or signs of illness. Although none of the mice developed detectable lesions, they did develop specific anti-T. pallidum antibodies that were observed as early as 21 days after inoculation with viable T. pallidum. The antibodies were detected by an enzyme-linked immunosorbent assay and by passive haemagglutination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…To evaluate the utility of a murine model for experimental syphilis, we first set out to confirm and expand previous work involving WT mice [10], [14], [15], [16], [21]. Our total inoculum (1×10 8 organisms) was slightly higher than that used previously [10], [14], [15], [16], [21] and was delivered at four sites (intragenital, intrarectal, intraperitoneal, and intradermal) in each animal in order to maximize the likelihood of establishing infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the utility of a murine model for experimental syphilis, we first set out to confirm and expand previous work involving WT mice [10], [14], [15], [16], [21]. Our total inoculum (1×10 8 organisms) was slightly higher than that used previously [10], [14], [15], [16], [21] and was delivered at four sites (intragenital, intrarectal, intraperitoneal, and intradermal) in each animal in order to maximize the likelihood of establishing infection.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the use of outbred animals, which cannot easily be genetically manipulated, poses serious limitations, which are compounded further by the lack of reagents for studying inflammatory processes in rabbits. In the mid-twentieth century, investigators reported that mice could be infected with T. pallidum and that spirochetes persist within inoculated mice; however, unlike rabbits, symptomatic infection was not observed [10], [14], [15], [16]. In 1980, Klein and colleagues [17] reported that certain mouse strains develop cutaneous lesions after T. pallidum inoculation, an observation that was enhanced in the presence of ionizing radiation; however, these findings have never been reproduced [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that certain strains of inbred mice infected with T pallidum do not develop a characteristic lesion, although the organism appears to persist within mouse tissue for several months after infection. 4 In addition, inbred mice injected with virulent T pallidum develop an appreciable humoral immune response as shown by the enzyme linked immunosorbent assay (ELISA) and the microhaemagglutination (MHA-TP) assay. 4 We were interested in investigating further the development of the humoral immune response in mice experimentally infected with Tpallidum to assess which Tpallidum antigens are recognised by serum from these mice and compare them with the antigens recognised by serum from rabbits and man infected with T pallidum.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, inbred mice injected with virulent T pallidum develop an appreciable humoral immune response as shown by the enzyme linked immunosorbent assay (ELISA) and the microhaemagglutination (MHA-TP) assay. 4 We were interested in investigating further the development of the humoral immune response in mice experimentally infected with Tpallidum to assess which Tpallidum antigens are recognised by serum from these mice and compare them with the antigens recognised by serum from rabbits and man infected with T pallidum. We also investigated the effect of antibiotic treatment on the antibody response of mice infected with Tpallidum.…”
Section: Introductionmentioning
confidence: 99%